Feasibility Study of Designing and Implementing Performance Budgeting in the Iranian Public Universities and Academic Institutions: The Case of the Sharif University of Thechnology - Mashayekhi, Bita; Mostafa SeyedHosseini, Seyed; Attaran, Navid (INTERNATIONAL JOURNAL OF MANAGEMENT & INFORMATION TECHNOLOGY, 2013)
The role of budgeting in governmental universities is vital since it affects youth generation. According to recent article passed by education ministry of Iran fundamental changes in universities management is required. In this study Sharif University of Thechnology has been chosen as a case study, obstacles in are identified and relatively a solution is proposed. The result indicates the necessity of implementing performance budgeting in this university.